Rodzina w poglądach działaczy i teoretyków galicyjskiej socjalnej demokracji - Jamrożek, Wiesław (Karkonoska Państwowa Szkoła Wyższa, 2011)
In the times of Galician autonomy the socialist movement, with its birth dating back to the 1860's and 1870's, played a major role in the political and social life under Austrian occupation. Socialism was a source of concern, dislike and outward hostility for many social circles in Galicia (as well as other regions of Poland), especially those of conservative social and political views. In those circles o certain negative stereotype of a socialist was formed. „A dark view of futurę revolutionary model of family and marriage” was an important element of the stereotype of the socialist as popularised by groups sceptical of socialism
Keywords: rodzina; Galicja; socialdemokracja